Immunocytolocalization of extensin in developing soybean seed coats by immunogold-silver staining and by tissue printing on nitrocellulose paper (The Rockefeller University Press, 1987)
In soybean seed coats the accumulation of the hydroxyproline-rich glycoprotein extensin is regulated in a developmental and tissue- specific manner. The time course of appearance of extensin during seed development was studied by Western blot analysis and by immunogold- silver localization. Using these techniques extensin was first detected at 16-18 d after anthesis, increasing during development to high levels at 24 d after anthesis. Immunogold-silver localization of extensin in the seed coat showed marked deposition of the glycoprotein in the walls of palisade epidermal cells and hourglass cells. The immunolocalization of extensin in developing soybean seeds was also made by a new technique--tissue printing on nitrocellulose paper. It was found that extensin is primarily localized in the seed coat, hilum, and vascular elements of the seed.